Extremophiles and extremozymes in lignin bioprocessing. (April 2022) - Zhu, Daochen; Qaria, Majjid A.; Zhu, Bin; Sun, Jianzhong; Yang, Bin
Abstract: Lignin is the most abundant aromatic biopolymer resource in nature. Due to its complexity and highly polymerized aromatic structure, lignin is strenuous to be merely degraded by normal microorganisms. Lignin-degrading microbes from extreme environments are considered suitable candidates for lignin bioprocessing. The heterogeneity of the depolymerized products hinders its biorefinery and high-value utilization of its potential products. The complexity and diversity of lignin biodegradation pathways require an arsenal of versatile lignin-degrading enzymes, including lignin peroxidase, laccase, manganese peroxidase, dye decolorizing enzyme, dehydrogenase, superoxide dismutase, cytochrome oxidase, monooxygenase, dioxygenase, O -demethylase, and methyltransferase. Several of these extremozymes were isolated from extremophiles, which are characterized by their activity under extreme conditions. The advantages of extremophiles and extremozymes rely on their capacity to withstand harsh environmental conditions, thus display superior performance, under favorable conditions in biomass pretreatment, lignin depolymerization, biotransformation and chemical production processes. Therefore, extremophiles and extremozymes are indeed very promising for efficient degradation and utilization of lignin. However, due to the particular physiological characteristics of extremophiles and their enzymes and the lack of tailored molecular biological tools, it is more challenging to study these microorganisms than ordinary microorganisms. Integrated transcriptomics, proteomics and metabolomics analysis of ligninolytic extremophiles is expected to unleash functional aspects of lignin biotransformation. In addition, heterologous expression of genes and operons from extremophiles in industrially relevant bacterial and fungal strains are required. Highlights: Extremophiles and extremozymes are favored in biomass pretreatment. Extremophiles and extremozymes are potential entities in lignin bioprocessing. Lignin valorization into the industrial scale could be achieved using extremozymes. Multi-omics and synthetic biology are useful approaches to explore new extremozymes.